High Throughput mRNA Sequencing Reveals Potential Therapeutic Targets of Tao-Hong-Si-Wu Decoction in Experimental Middle Cerebral Artery Occlusion - Duan, Xianchun; Han, Lan; Peng, Daiyin; Chen, Weidong; Peng, Can; Xiao, Ling; Bao, Qiuyu (Frontiers in Pharmacology, 2019)
Both experimental and clinical studies showed that the effect of Tao-Hong-Si-Wu decoction (THSWD) on neurological deficit Middle Cerebral Artery Occlusion (MCAO) was improved. However, the multifaceted mechanism of THSWD in MCAO has not yet been fully understood. In this study, mRNA transcriptome was used to study various therapeutic targets of THSWD. Methods: RNA-seq was applied to identify differentially expressed genes (DEGs). MCAO-induced up-regulated genes (MCAO vs control) and THSWD-induced down-regulated genes (THSWD compared to MCAO was performed up-regulated) were identified. The intersection gene were defined as up-regulated differentially expression genes (up-DEGs) which between these 2 sets was determined to identify MCAO-induced highly expressed genes that were reversed by THSWD. Afterwards, down-regulated genes induced by MCAO and up-regulated genes triggered by THSWD were in the formation of another series of intersections, based on which, biological functions and signaling pathways were determined by gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) pathway analyses. In addition, several identified genes were validated by RT-qPCR. Results: There were total of 339 DEGs filtered based on 2 series (MCAO vs control and MCAO vs THSWD), which were enriched in the cell cycle (rno04110), ECM-receptor interaction (rno04512), complement and coagulation cascades (rno04610), focal adhesion (rno04510), hematopoietic cell lineage (rno04640), Neuroactive ligand-receptor interaction (rno04080), Cocaine addiction (rno05030), Amphetamine addiction (rno05031), Nicotine addiction (rno05033), Fat digestion and absorption (rno04975), Glycerophospholipid metabolism (rno00564), etc. The PPI network consisted of 202 nodes and 1,700 connections, and identified two main modules by MOCDE. Conclusion: The cell cycle (rno04110), ECM-receptor interaction (rno04512), complement and coagulation cascades (rno04610), focal adhesion (rno04510), hematopoietic cell lineage (rno04640), Neuroactive ligand-receptor interaction (rno04080) are potential therapeutic targets of THSWD in MCAO. The aim of this essay is to prevent long-term neurological deficits after intracerebral hemorrhage. The article provided a theory basis for THSWD to prevent long-term neurological deficits after intracerebral hemorrhage.